Análisis de los consumos históricos de agua potable del cantón La Troncal provincia del Cañar - Cali Parco, Wilmer Eduardo (2023)
For many years, the design of drinking water and sewerage systems in Ecuador was based on the CPE INEN 005-9-1 standard, which has not received significant changes or updates for more than 30 years. This is one of the reasons why the standard suggests carrying out specific studies for cantons, towns, and cities with the objective of obtaining data adjusted to the population reality of the cantons, cities, parishes, etc., in relation to water consumption in order to carry out optimal sewerage and drinking water design. In this research, the drinking water consumption readings of the canton La Troncal were compiled, with which a value of the coefficient of variation of consumption was determined that can be used for the design of drinking water and sewerage systems. The research is part of and contributes to the project "Determination of the variation of drinking water consumption in cities with less than 150,000 inhabitants in Ecuador". For this research, a structured quantitative method was employed using statistical tools (Minitab) with which the following tests were carried out: normality and homoscedasticity tests, analysis of variances, Tukey tests, interval diagrams, and descriptive diagrams. The results show that the coefficient of variation of consumption (Kd) found for the canton of La Troncal is within the range established by the INEN standard of 1.3 to 1.5.